PENGELOLAAN KELAS DALAM PEMBELAJARAN BAHASA INDONESIA DI KELAS VIII SMP NEGERI 10 KOTA BENGKULU TAHUN AJARAN 2016/2017 - Githa Ulandari; Suhartono Suhartono; Arono Arono (Jurnal Korpus, 2017)
Classroom management is a real effort to realize an effective teaching or learning process. With good class management is expected to support the achievement of learning objectives and provide a positive influence that directly support the implementation of teaching and learning in the classroom. In order to provide encouragement and stimulus to students in learning, the class needs to be managed as well as possible. Activities that need to be implemented in managing the class, namely the arrangement of students in the classroom, spatial arrangement, creating classroom discipline, showing attitude responsiveness.This study aims to determine the management of classes in Indonesian subjects related to the maintenance of optimal learning conditions (preventive) Learning conditions (repressive). Data collection with observation of learning process observation. Interviews with relevant subject teachers, and with a study of the form of a learning program plan (RPP). The results obtained, then analyzed based on the method of observation and documentation studies and. The results showed that classroom management in Indonesian language subjects in SMP Negeri 10 Bengkulu city related to the maintenance of optimal learning (preventive) which consists of 6 aspects and return of learning condition (repressive) consisting of 3 aspects already implemented by the teacher.